EFFORTS TO INCREASE CHILDREN'S ABSORPTIONAL Capacity THROUGH THE CHARACTER EDUCATION PROGRAM AT KB-TK ARRAHMAN ISLAMIC SCHOOL - Abdullah, Jannati; Sari, Siti Mayang (Sensei International Journal of Education and Linguistic, 2024)
Early childhood education (PAUD) at KB-TK Arrahman Islamic School plays a major role in forming the foundations of children's character and attitudes towards life. In this complex era of globalization, character education is an urgent need to give children the right tools to face the dynamics and challenges of the future. This research aims to evaluate the condition of children's absorption of Islamic values in this school, identify Islamic character values that are considered essential, and develop strategies and character education programs that can be integrated holistically in the PAUD curriculum. This research uses descriptive qualitative methods. Based on the results of interviews, it shows that children respond positively to Islamic values, with active support from parents and teachers. Even though they are faced with challenges such as limited resources, schools face them with creativity and collaboration, creating an educational environment that supports children's Islamic character through targeted and responsive programs. A comprehensive evaluation is carried out to measure the level of children's understanding of these values. The next steps include identifying essential Islamic character values, developing character education strategies and programs, and actively involving parents in the education process. With this understanding, schools can design programs that are more targeted and responsive to children's needs, creating an educational environment that supports the development of their Islamic character through collaboration between schools, parents and local resources.